2016
DOI: 10.1016/j.cell.2016.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoribosylation of Ubiquitin Promotes Serine Ubiquitination and Impairs Conventional Ubiquitination

Abstract: Conventional ubiquitination involves the ATP-dependent formation of amide bonds between the ubiquitin C terminus and primary amines in substrate proteins. Recently, SdeA, an effector protein of pathogenic Legionella pneumophila, was shown to mediate NAD-dependent and ATP-independent ubiquitin transfer to host proteins. Here, we identify a phosphodiesterase domain in SdeA that efficiently catalyzes phosphoribosylation of ubiquitin on a specific arginine via an ADP-ribose-ubiquitin intermediate. SdeA also cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
338
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 267 publications
(349 citation statements)
references
References 64 publications
10
338
1
Order By: Relevance
“…This revealed that the Arg42 residue in ubiquitin that becomes modified is located too far away from the ribose group of NADH for modification to occur directly . By contrast, another of ubiquitin's arginine residues, Arg72, which was previously shown to be important in SdeA-mediated ubiquitination 7 , is located much closer to the enzyme-bound NADH. The authors used computer simulations of the complex, called molecular dynamics, to show that Arg72 and one other arginine residue (Arg74) anchor ubiquitin to mART.…”
mentioning
confidence: 74%
See 4 more Smart Citations
“…This revealed that the Arg42 residue in ubiquitin that becomes modified is located too far away from the ribose group of NADH for modification to occur directly . By contrast, another of ubiquitin's arginine residues, Arg72, which was previously shown to be important in SdeA-mediated ubiquitination 7 , is located much closer to the enzyme-bound NADH. The authors used computer simulations of the complex, called molecular dynamics, to show that Arg72 and one other arginine residue (Arg74) anchor ubiquitin to mART.…”
mentioning
confidence: 74%
“…Isolating a sufficient number of nanoribbons that have perfect zigzag edges to enable their magnetic characterization is extremely challenging, and so the data from such studies 6 are scarce and inconclusive. Experiments performed on single graphene layers prepared in situ under a high vacuum have revealed the formation of local electronic states at edges, but did not provide any evidence of magnetism 7 . By expanding a previously developed…”
Section: F E R N a N D O Lu I S And E U G E N I O C O R O N A D Omentioning
confidence: 99%
See 3 more Smart Citations